Integrated Data Hiding and Compression Scheme Based on SMVQ and FoE Inpainting. (2016) - Badr, Shahbaz; Noufal, P.
Abstract: Data Hiding and Compression are equivalently significant terms in the field of communication and its study is inevitable. In this paper, a novel joint data hiding and compression system is ventured based on VQ, SMVQ andimage inpainting. Data hiding and compression scheme are melded into a single unit which will increase the efficiency of communication. As a pre-processing step, the image is divided into non overlapping blocks. The topmost and leftmost blocks are compressed by employing VQ and the residual blocks are embedded with secret data and compressed simultaneously by SMVQ or image inpainting adaptively according to the secret bit to be hidden. VQ is also employed on a threshold basis for some blocks to control the distortion. The concatenated codes received are segmented into indices and secret bits according to the indicator bits. On the receiver side, FoE based inpainting was used for reconstructing lost parts of image. Experimental results validates satisfactory performance in terms of compression ratio and image quality.